Doing Time - Matthews, Roger. author. aut Link
XI, 297 p.
Keywords: The new edition of Doing Time brings this widely recognized book up-to-date and provides an accessible and informed discussion of current debates around prisons and penal policy. Drawing on a range of international material the book provides a critical sociological analysis of developments in imprisonment.